Plataforma Geoportour inovação tecnológica aplicada à educação patrimonial em Porto Nacional - TO - Alencar, Genias Brandão de (UFT, 2021)
Integrating the potential of digital technologies to heritage education presents itself as new alternatives to instrumentalize and contextualize learning, to bring the community closer to its cultural heritage and to increase its attractiveness. Following this perspective, this study aimed to develop a collection of computational resources integrated with a digital platform, called GeoPorTOur, as a proposal for technological innovation applied to heritage education in Porto Nacional – TO. Among the proposed resources, we highlight virtual visits through 360- degree images, a 3D modeling; a Quiz and a mobile application of the platform. The study, initially exploratory, sought to know through a literature review, the potential of digital technologies applied to heritage education and its relationship in the development of cultural tourism. It is also a descriptive research given the nature of its objectives, and is characterized as a research of the type applied for proposing a solution for the expansion of the actions of preservation and appropriation of the Cultural Heritage of Porto Nacional. To evaluate the initial proposal and the minimum viable product of the software with the community, an online questionnaire was made available through social networks (WhatsApp and Facebook), in which we sought to obtain the user's perception of functional aspects and potentialities of the Platform GeoPorTOur and its mobile application for the proposed solution. The obtained results in the execution of the development stages and in the evaluation of the tool, demonstrated that the overall objective of the research was reached. Therefore, it can be concluded that the computational resources added to the GeoPorTOur Platform can contribute to the expansion of heritage education actions, and consequently, help strategically for the development of cultural tourism in Porto Nacional.